Journal der Juristischen Zeitgeschichte (De Gruyter, 2009)
Legal contemporary history has been developing along the edges of legal studies, legal history, and general history. The methodology debate and research activities have expanded and intensified. Legal contemporary history can be applied as an instrument of legal political critique of current law and the Journal of Contemporary Legal History is dedicated to promoting this manner of understanding.